Jews of Badinan District : a Study of Their Populations , Cultural , Social and Economic Conditions from (1921-1951) (College of Basic Education Research Journal, 2025)
Current research dealt with  Jews of Badinan by shedding light on their population, residence clusters in  cities and villages of the region, in addition to their economic, social and cultural conditions during  monarchy, Origins of this community go back to Jews who were captured by  Assyrian kings during their campaigns on Palestine.  Jews worked in agriculture  animal husbandry, trade as well as being goldsmiths, weavers, tanners, etc. As for their social life, they had special laws, regulations, customs and traditions,  their temples spread in cities and some villages, not to forget to mention selected persons of  Jewish community to conduct their religious and worldly affairs. Jews  had their own  schools in  region that taught Students basics of Jewish religion.
Keywords: jews; Badinan; economic; Social; Dohuk; Zakho; Amadiya; Aqra